Laser Therapy Approaches in the Treatment of Kaposi’s Sarcoma: A Comprehensive Review of Dermatologic Options - Chiara Battilotti; Fortunato Cassalia; Francesca Svara; Alessandra Latini; Norma Cameli; Steven Paul Nisticò (Dermatology Practical & Conceptual)
Introduction: Kaposi sarcoma is a multicentric angioproliferative disease associated with human herpesvirus 8 and often exacerbated by immunosuppression. Effective treatment includes systemic and local therapies, with laser treatments gaining prominence in dermatological practice.